Food supplementation in distinct Corsican oak habitats and the timing of egg laying by Blue Tits - Bourgault, Patrice; Perret, Philippe; Lambrechts, Marcel M. (JOURNAL OF FIELD ORNITHOLOGY, 2009)
Resource constraints may impose physiological limitations on egg production and influence the timing of breeding in seasonally breeding birds. Food-supplementation experiments have demonstrated that food availability may influence the timing of egg laying, but the moderate response of birds in most studies suggests that the effect of food availability may be apparent only under certain ecological conditions. Experiments conducted in habitats that differ in ecological characteristics and natural availability of food sources are, therefore, needed to effectively examine the possible role of habitat-specific physiological constraints on the timing of breeding. We compared the response of Blue Tits (Cyanistes caeruleus) to supplemental feeding in four oak woodlands that differed in elevation, forest type, and food availability on the island of Corsica. We found that supplemental feeding advanced the date of egg laying (by about 1 week) at only one of four sites; a site dominated by evergreen holm oak where the availability of natural food was likely lower than at the other sites. Our results suggest that the response of Blue Tits to supplemental food depends on the natural level of resource abundance, but, in addition, that the effect of supplemental feeding on the timing of breeding appears to be small compared to the typical and, for our study sites, great (> 1.5 mo) between-population variation in clutch initiation dates. Physiological limitations related to the acquisition of nutrients and energy may exert only a limited effect on the onset of breeding, and behavioral flexibility in the integration of fine-scale environmental signals (e.g., temperature and phenology) that predict future breeding conditions may be more important in explaining variation among populations in the timing of breeding.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Blue tit; food constraints; food supplementation; proximate factors; timing of breeding